Глобалізація та міжнародна економіка: складність інтеграції ринків та економічні наслідки на рівні країн (український досвід) - Гетманець, О. П.; Hetmanets, O. P.; Коробцова, Д. В.; Korobtsova, D. V.; Єжелий, Ю. О.; Yezhelyi , Yu. O.; Гетманець Ольга Петрівна; Коробцова Дар'я (Академічні візії. - 2023. - Вип. 20., 2023)
У цій статті описано характеристики, позитивні риси та ризики сучасного процесу глобалізації, а також ризики для національних економік. Процес міжнародної економічної глобалізації значною мірою торкнувся України і позитивно впливає на всі аспекти її економічного розвитку, завдяки чому Україна поступово займає своє місце в новій системі міжнародних економічних відносин. Метою статті є висвітлення сутності глобалізації та її економічних наслідків для країн, а саме для України. Участь України в глобальному ринку є дуже ймовірною, але вона має як позитивні, так і негативні наслідки. Наша держава вступила в процес глобалізації з недостатньою економічною підготовкою. Тому пріоритетним завданням України є наближення її економіки до рівня провідних країн світу шляхом посилення інноваційних процесів, стимулювання бізнесу та надання всебічної підтримки підприємництву, покращення інвестиційного клімату, адаптації правової системи до сучасного бізнес‐середовища.

This article describes the characteristics, positive features and risks of the modern process of globalization, as well as risks for national economies. Globalization is one of the most pressing problems of our time, as it characterizes the state and development of the economic system as a whole. Most researchers note that the impact of the globalization process on national economies is very complex and contradictory. In modern conditions, national economies are increasingly dependent on external factors, especially in the conditions of lowering trade barriers and expanding access to global capital markets. The process of international economic globalization is not inviolable for Ukraine, it is gradually taking its place in the new system of international economic relations and has a positive effect on all aspects of Ukraine’s economic development. The purpose of the article is to highlight the essence of globalization and its economic consequences for countries, namely for Ukraine. Ukraine is integrated into global international relations and projects, which leads to an increase in investment attractiveness for foreign organizations and private investors. The acceleration of these processes should be facilitated by an effective state macroeconomic policy aimed at creating a favorable investment climate for conducting business and protecting property rights. Ukraine’s participation in the global market is very likely, but it has both positive and negative consequences. Our state entered the process of globalization with insufficient economic preparation. Therefore, Ukraine’s priority task is to bring its economy closer to the level of the world’s leading countries by strengthening the innovation process, increasing incentives for doing business, improving the investment climate, adapting the legal system to the modern business environment, and providing comprehensive support to entrepreneurship. These and other related issues with the development of the national economy of Ukraine in the context of current and future global challenges, should become the subject of further scientific research.

Описаны характеристики, положительные качества и риски современного процесса глобализации, а также риски для национальных экономик. Процесс международной экономической глобализации в значительной степени затронул Украину и положительно влияет на все аспекты ее экономического развития, благодаря чему Украина постепенно занимает свое место в новой системе международных экономических отношений. Освещена сущность глобализации и ее экономических последствий для стран, а именно для Украины.
Globalization and the international economy: complexity of market integration and economic consequences at the country level (Ukrainian experience)
Keywords: глобалізація; економічна глобалізація; інтеграція; національна економіка; конкурентоспроможність; регіоналізація; Україна; globalization; economic globalization; integration; national economy; competitiveness; regionalization; Ukraine; глобализация; экономическая глобализация; интеграция; национальная экономика; конкурентоспособность; регионализация; Украина